Perspective, Metaphor and Hermeneutics - Serrano Ribeiro, José L. (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
A productive way of approaching the problem arising from the relations between subject, language and reality, is relying on a perspectivist theory, like the one by Ortega, of a great ontological, phenomenological and hermeneutic solidity. The human environment is conditioned by desires, perspectives and words, requiring the subject to maintain new links with reality, the others and himself. In this context the metaphoric process is imposed as the most authentic way of being, interpreting and speaking. But we must not forget the other side of the metaphor, because while it is an effective device for interpretation, it also possesses the power to hide, depending on the perspective used. Thus, the subject appears as an unfinished work of metaphoric process, the interpretations and the symbols, which, while being handled, handle the very subject, producing an integrated system with language and reality.
Keywords: desire; hermeneutics; language; metaphor; perspective; reality; subject